(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Maternal hypotension after spinal anaesthesia for caesarean delivery remains a major problem. Different techniques are used to counteract this deleterious effect. Different studies showed that colloid is a better preload solution in comparison to crystalloid for the prevention of post-spinal hypotension. The aim of the current study was to find the effects of volume preload with either crystalloid or colloid on changes in maternal blood pressure and neonatal outcome during elective caesarean section. Materials and and methods: This open-label Randomized clinical trial was carried out in the Obstetrics and Gynaecology Department of Chittagong Medical College Hospital (CMCH) during the period January December 2017. One hundred and ten subjects, who were admitted for the elective caesarean section, were selected as per inclusion and exclusion criteria, and randomly assigned to one of the two groups after written informed consent had been obtained from each patient. Fifty-five subjects in each group received preload either with Hartman’s solution (Group A) or hydroxyethyl starch 6% (Group B) before induction of spinal anaesthesia. The incidence of hypotension (Systolic blood pressure 20% to 30% fall from baseline) and the amount of ephedrine used to treat hypotension were compared. Neonatal outcome was measured by Apgar score at 1 and at 5 minutes after delivery. Results: There was no difference in the demographic and gestational characteristics between the two groups. Baseline blood pressure was also comparable between the two groups. The sample size was 108 (53 in Group A and 55 in Group B) because 2 patients in Group A spinal induction failed. Incidence of hypotension (43.39% vs. 29.09%) and required dose of ephedrine (12.19mg vs. 10 mg) was more in the crystalloid group than colloid but these differences were not statistically significant (p>0.05). The frequency of perioperative nausea and vomiting was also similar in both groups (p>0.05). Apgar scores of all babies were more than 7 at 1 and 5 minutes after delivery. There was no significant difference in Apgar score between the two groups (p>0.05). Conclusion: The results of the present study concluded that there was no significant difference between crystalloid and colloid groups in development of post-spinal hypotension during caesarean section. JCMCTA 2024 ; 35 (1) : 22-27